A Resident Narrative Medicine Curriculum to Promote Professional Identity Development: Story-Based Sessions Grounded in Narrative Learning Theory - Michelle Silver; Farah Hussain (Association of American Medical Colleges, 2024)
Introduction Empathy, reflection, and social connectedness are important skills for physician identity development and are increasingly challenged by burnout. Humanities-based interventions like narrative medicine (NM) are emerging in medical education to promote these skills. Only 17% of such initiatives target graduate medical learners. Furthermore, interventions are inconsistent in approach and theory representation. NM uses story-based learning to promote reflection and group discussion. Inspired by narrative learning theory, we developed NM sessions for residents to foster healthy identity development. Methods Ninety-minute sessions were integrated into curricula for PGY 1-PGY 3 internal medicine-primary care residents at two large academic centers. Sessions involved engagement with a narrative source (stories, poems, art), personal reflection, and group discussion. Topics ranged from burnout to difficult patients. Participants completed anonymous postsession surveys assessing satisfaction, attitudes, and skills. Results Fifteen sessions occurred from 2021 to 2023, with three to 10 residents per session. Fifty residents completed between one and four sessions, with 68 survey responses (response rate: 88%). Over 95% ranked 4-5 out of 5 for overall impression (n = 67) and personal value (n = 65) of sessions. Sessions were highly enjoyable (M = 4.8), with mean scores of >4 out of 5 for impact on wellness, appreciation of work values, social connectedness, and patient care. Discussion NM sessions demonstrated measurable improvements in several domains of professional performance including wellness, job satisfaction, and patient care, while promoting camaraderie and emotion processing. Our materials offer tremendous potential for promoting healthy identity formation.